OPTICAL SIGNATURE of WOOD SAMPLE WITH DIFFERENT SCATTERING ANGLES BY USING MUELLER MATRIX (International Journal of Food and Nutritional Sciences, 2022)
Mueller Matrix Detection Polarimetry is a highly effective imaging technique that provides precise measurements of Mueller matrices in each detected image pixel. The employed technology obtains 16 Mueller Matrix pictures, which are then processed to look at the sample's polarization properties. This discussion describes the optical setup used to capture the Mueller Matrix Images operating in reflection frame, and presents the resulting polarization characteristics for the same wood sample under a selection of scattering angles.